HUBUNGAN TINGKAT PENGETAHUAN TENTANG KEPUTIHAN DENGAN PENANGANAN KEPUTIHAN PADA SISWI KELAS X SMK YPE SUMPIUH KABUPATEN BANYUMAS TAHUN 2018 - Tanti Fitriyani; Wiji Oktanasari (Kesmas Indonesia, 2019)
ABSTRACT One of the clinical complaint from adolescent reproduction is leucorrhea. Leucorrhea is vagina’s liquid expenditure that not shaped blood. It is sometimes caused infection that always wet and make irritation, feel itchy and disturbance to the sufferer. The purpose of this research is to know about relation between knowledge of leucorrhea and handling of leucorrhea in student of SMK YPE Sumpiuh 2018 grade X, Banyumas regency. This research use analytic survey method with cross sectional approach. The subject of this research is students of SMK YPE Sumpiuh grade X. The number of students are 71 person. The analysis method of the statistic that used is chi square. The result from this research is 42 student (59,2%) have good level of knowledge about leucorrhea. And 39 student (54,9%) can handles leucorrhea correctly. The Conclusion of his research is there any relationship between knowledge of leucorrhea and handling of leucorrhea in class of student SMK YPE Sumpiuh grade X (c2hitung=5,722> c2tabel=3,481). Keyword : level of knowledge, leucorrhea handling. Bibliography : 29 ( 2005-2016)